Tracheomalacia and breath holding: a case report. Issue 4 (1st October 2000) - Griffiths, H; Doull, I; Williams, R G; Marnane, C
Abstract : A child with a long standing history of cyanotic breath holding attacks presented with acute respiratory distress. Subsequent investigation established that her clinical condition was caused by tracheomalacia. We hypothesise that tracheomalacia might be an under recognised contributor to cyanotic breath holding attacks, the pathogenesis of which is poorly understood.